2015
DOI: 10.1111/bcp.12785
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing some older drugs that cross the blood–brain barrier and have potential anticancer activity to provide new treatment options for glioblastoma

Abstract: Glioblastoma is a brain neoplasm with limited 5‐year survival rates. Developments of new treatment regimens that improve patient survival in patients with glioblastoma are needed. It is likely that a number of existing drugs used in other conditions have potential anticancer effects that offer significant survival benefit to glioblastoma patients. Identification of such drugs could provide a novel treatment paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Our study supports the results of that analysis, examining a nation-wide, unselected patient material that reflects nationwide prescription trends and not the preferences of individual clinicians or hospitals. A retrospective in vivo study of GBM survival according to AED use has been warranted [32]. The present study clarifies the issue as none of the six AEDs we investigated had any positive effect on OS.…”
Section: Does the Choice Of Aed Affect Survival?supporting
confidence: 57%
“…Our study supports the results of that analysis, examining a nation-wide, unselected patient material that reflects nationwide prescription trends and not the preferences of individual clinicians or hospitals. A retrospective in vivo study of GBM survival according to AED use has been warranted [32]. The present study clarifies the issue as none of the six AEDs we investigated had any positive effect on OS.…”
Section: Does the Choice Of Aed Affect Survival?supporting
confidence: 57%
“…Repurposed drugs used to treat other medical conditions have demonstrated potential anticancer activity for the treatment of GBM. 5 In the current phase 1 trial in patients with newly diagnosed GBM, we observed that the combination of TMZ with 1 or more repurposed drugs (mefloquine, memantine, and metformin) was feasible and overall well tolerated.…”
Section: Discussionmentioning
confidence: 89%
“…4 Various repurposed drugs that cross the blood-brain barrier, such as psychotropic, antiepileptic, and antihypertensive drugs, have been investigated as potential treatments for GBM. 5 Because of its favorable safety profile, TMZ has been used in combination therapeutic regimens with repurposed drugs such as interferon, thalidomide, isotretinoin, celecoxib, and marimastat for gliomas in clinical trials, with promising preliminary results. [6][7][8][9][10][11] In preclinical studies, N-methyl-D-aspartic acid antagonists, including memantine, inhibit proliferation in GBM, medulloblastoma cell lines, 12,13 and high-grade gliomas in vivo 12,14 by reducing tumor expansion, possibly through the neuroprotection of peritumoral tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Pitavastatin reduced the irinotecan IC50 by 40 to 70-fold (Jiang et al, 2014). Additionally, the repurpose of antihypertensive, beta-blockers (Rundle-Thiele et al, 2016), antidiabetics (Wurth et al, 2013) and anti-alcoholism (Triscott et al, 2012) drugs for GBM adjuvant treatment also demonstrated good potential. As these drugs already have known properties and are approved by drug administration agencies, the clinical application could be facilitated and benefit patients earlier than developing a new drug.…”
Section: New Therapies and Future Prospectivementioning
confidence: 99%